Thickened oil thermal mining polymer blocking agent and preparation method thereof

By using heavy oil hot mineral polymer sealant prepared by mineral polymers and other materials, the problems of high water content and steam flow in heavy oil hot production are solved, and the effect of effective sealing and improving recovery is achieved.

CN119592311APending Publication Date: 2025-03-11大城鼎立(北京)科技发展有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411693875.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

There is a high water content and serious steam traversal phenomenon in heavy oil hot production, resulting in a decrease in the cyclical output and oil-gas ratio, making it difficult to stabilize production. The existing plugging agent technology has problems such as low intensity, short pumping cycle and short validity period, which is difficult to promote and apply on a large scale.

Method used

A heavy oil thermal mineral polymer sealant is prepared by using mineral polymer as the main material, combining an exciter, a water reducer, a suspension stabilizer and a retarder, which has excellent properties such as high strength, high temperature resistance, low shrinkage and low expansion.

Benefits of technology

The sealing agent can effectively seal the traverse and effluent channels, reduce the water content of the oil well, improve the final recovery rate of the heavy oil field, and has long-term and high operability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005151652950000061
    Figure BDA0005151652950000061
  • Figure BDA0005151652950000062
    Figure BDA0005151652950000062
  • Figure BDA0005151652950000063
    Figure BDA0005151652950000063
Patent Text Reader

Abstract

The invention provides a heavy oil thermal mining polymer plugging agent and a preparation method thereof, and relates to the technical field of oilfield chemical plugging, the raw materials comprise blast furnace slag, coal-fired slag, an exciting agent, a water reducing agent, a suspension stabilizer and a retarder; wherein the exciting agent is a mixture of sodium hydroxide and water glass, the modulus of the water glass in the exciting agent is 1.3-1.5, and the adding amount of the exciting agent is 20%-25% of the total weight of the blast furnace slag and the coal-fired slag. The raw material preparation process is simple, the field operability is high, the prepared heavy oil thermal mining polymer plugging agent is added into water and fully stirred to prepare a solution, the solution is cured under the action of a certain temperature to form a high-strength high-temperature-resistant concrete-shaped solid substance, effective plugging is formed in a channeling layer and a water outlet channel, the plugging validity period is long, and the plugging effect is good. And the final recovery efficiency of a heavy oil field is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of oilfield chemical plugging, and in particular to a heavy oil thermal mining material polymer plugging agent and a preparation method thereof. Background Art

[0002] Heavy oil thermal recovery has entered the middle and late stages of multiple rounds of steam huff and puff development. Steam channeling and high water-content wells have gradually increased, and the periodic production and oil-gas ratio have decreased. It is difficult to maintain stable production, which has become the main problem restricting the development of heavy oil. The existing problems include: 1. In the high water content, medium-high rounds, and medium-high production stages, the periodic oil-gas ratio decreases from round to round; 2. The number of high water-content wells has increased year by year, and there are problems such as small water plugging and oil increase and short effective period; 3. The reservoir is highly heterogeneous, the well spacing is small, the contradictions within the layer are prominent, and the steam channeling phenomenon is serious.

[0003] At present, the commonly used plugging and adjusting technologies such as nitrogen foam, composite high-temperature foam, thermosensitive gel plugging agent, temperature-resistant organic gel plugging agent and solidified particle plugging agent have low plugging agent strength, short pumping cycle or short validity period, and are difficult to promote and apply on a large scale. Therefore, it is very necessary to introduce a high-temperature resistant and high-strength composite plugging agent to block the steam channel, improve the steam absorption profile and liquid production profile, control water and stabilize oil, and improve the recovery rate of heavy oil reservoirs. Summary of the invention

[0004] In view of this, the embodiment of the present application provides a heavy oil thermal mining polymer plugging agent and a preparation method thereof, which has a simple raw material preparation process and strong on-site operability, can form effective plugging in crossflow and water outlet channels, reduce water content in oil wells, and improve the ultimate recovery rate of heavy oil fields.

[0005] The embodiment of the present application provides the following technical solution: a polymer plugging agent for heavy oil hot mining, the raw materials of which include: blast furnace slag, coal-fired furnace slag, an activator, a water reducer, a suspension stabilizer, and a retarder; wherein the activator is a mixture of sodium hydroxide and water glass, the modulus of the water glass in the activator is 1.3 to 1.5, and the addition amount of the activator is 20% to 25% of the total weight of the blast furnace slag and the coal-fired furnace slag.

[0006] The present invention provides a heavy oil thermal mining material polymer plugging agent, which is a novel high temperature resistant and long-acting plugging material with a mineral polymer material as a main agent, and is prepared by mixing a mineral polymer material to adjust the channel permeability, a suspension stabilizer to improve the stability and pumpability of the system, and a retarder to extend the solidification time at high temperature. The solution is solidified in the formation by using the formation thermal energy to form a high-strength high temperature resistant concrete-like solid material, which effectively blocks the crossflow and water outlet channels, reduces the water content of the oil well, and improves the final recovery rate of the heavy oil field.

[0007] Geopolymer is a new type of inorganic non-metallic material that has been active in recent years. Geopolymer is mainly composed of natural minerals such as silicate and lithium magnesium salt. Its structure is similar to the three-dimensional grid structure of organic polymers. Its main body is [SiO4] and [AlO4] tetrahedron, and alkali metal or alkaline earth metal ions are distributed between the network pores to balance the electric charge.

[0008] Heavy oil thermal mining polymer plugging agent uses mineral polymer as the main material, which has the following functions: (1) excellent acid and alkali corrosion resistance; (2) low permeability, can solidify toxic waste; (3) low shrinkage and low expansion rate. The shrinkage of inorganic mineral polymer at 7d and 28d is only 0.2% and 0.5% respectively, the linear shrinkage at 400℃ is 0.2%~1%, and the linear shrinkage at 800℃ is 0.2%~2%. Its linear expansion coefficient is 2.1×10-6 / ℃~4.5×10-6 / ℃ at 0-1000℃; (4) high temperature resistance and low thermal conductivity.

[0009] According to one embodiment of the present application, the weight ratio of the coal-fired furnace slag to the blast furnace slag is 1:1.

[0010] According to one embodiment of the present application, the chemical composition of the blast furnace slag includes, by mass percentage: 32.0-49.0% CaO, 32.0-41.0% SiO2, 6.0-17.0% Al2O3, 0.2-4.0% Fe2O3, 2.0-13.0% MgO, 0.1-4.0% MnO, 0.2-2.0% S, and the remainder is loss on ignition.

[0011] According to an embodiment of the present application, the chemical composition of the coal-fired slag includes, by mass percentage: 49.2-62.5% SiO2, 15.1-25.2% Al2O3, 5.1-16.1% Fe2O3, 0.7-4.9% CaO, 9.5-1.8% MgO, 1.3-2.8% K2O, and the remainder is loss on ignition.

[0012] According to an embodiment of the present application, the particle sizes of the coal-fired furnace slag and the blast furnace slag are both 3 to 10 μm.

[0013] According to an embodiment of the present application, the added amount of the water reducer is 3 to 3.5% of the total weight of the blast furnace slag and the coal-fired furnace slag; wherein the water reducer is a lignin sulfonate water reducer.

[0014] According to an embodiment of the present application, the added amount of the suspension stabilizer is 20-30% of the total weight of the blast furnace slag and the coal-fired furnace slag; wherein the suspension stabilizer is 2-acrylamido-2-methylpropane sulfonic acid.

[0015] According to an embodiment of the present application, the added amount of the retarder is 5-20% of the total weight of the blast furnace slag and the coal-fired furnace slag material; wherein the retarder is sodium gluconate.

[0016] According to one embodiment of the present application, the raw materials for preparing the heavy oil thermal mining polymer plugging agent include, by weight percentage: 50 parts of blast furnace slag, 50 parts of coal-fired furnace slag, 20 parts of activator, 3 parts of water reducer, 25 parts of suspension stabilizer, and 15 parts of retarder.

[0017] The present application also provides a method for preparing the polymer plugging agent for heavy oil thermal mining as described above, the method comprising: taking blast furnace slag and coal-fired furnace slag according to a ratio, and stirring and mixing them to obtain a dry material A; adding an activator, a water reducer, a suspension stabilizer and a retarder to the dry material A in proportion, stirring them thoroughly and evenly, and grinding to obtain the polymer plugging agent for heavy oil thermal mining.

[0018] Compared with the prior art, the beneficial effects that can be achieved by at least one of the above-mentioned technical solutions adopted in the embodiments of this specification include at least the following: a heavy oil thermal mining polymer plugging agent according to the embodiment of the present invention has the following excellent properties: (1) deep plugging can be achieved according to the reservoir conditions; (2) the preparation process is simple, the pumping cycle is long, the sealing time is adjustable, and the field operability is strong; (3) the high temperature resistant plugging ability is strong, which can reach above 300°C; (4) the plugging effective period is long, and the effective plugging time can reach more than several years, which effectively avoids repeated operations on the same layer; (5) the system has good stability and a large volume retention rate after solidification, which avoids the complexity of construction caused by sedimentation, volume shrinkage, etc.; (6) strong chemical corrosion resistance and strong interface bonding ability; (7) high strength after solidification, which can meet the subsequent operations of wells with higher pressure requirements.

[0019] The heavy oil thermal mining polymer plugging agent obtained by the preparation method of the embodiment of the present invention is added to water and fully stirred to form a solution. Under a certain temperature, the solution solidifies to form a high-strength high-temperature resistant concrete-like solid substance, which can effectively plug the channeling layer and the water outlet channel, reduce the water content of the oil well, and improve the final recovery rate of the heavy oil field. DETAILED DESCRIPTION

[0020] The embodiments of the present application are described in detail below.

[0021] The following describes the implementation methods of the present application through specific examples, and those skilled in the art can easily understand other advantages and effects of the present application from the contents disclosed in this specification. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all the embodiments. The present application can also be implemented or applied through other different specific implementation methods, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present application. It should be noted that, in the absence of conflict, the following embodiments and the features in the embodiments can be combined with each other. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without making creative work belong to the scope of protection of the present application.

[0022] The embodiment of the invention discloses a polymer plugging agent for heavy oil thermal mining and a preparation method thereof. The raw materials of the polymer plugging agent for heavy oil thermal mining include: blast furnace slag, coal-fired slag, activator, water reducer, suspension stabilizer and retarder.

[0023] Example 1

[0024] In this embodiment, the raw materials for preparing the heavy oil hot mining polymer plugging agent include, by weight percentage: 50 parts of blast furnace slag, 50 parts of coal-fired slag, 20 parts of activator, 3 parts of water reducer, 25 parts of suspension stabilizer, and 15 parts of retarder. The activator is a mixture of sodium hydroxide and water glass, the modulus of the water glass in the activator is 1.3-1.5, the water reducer is lignin sulfonate water reducer, the suspension stabilizer is 2-acrylamido-2-methylpropane sulfonic acid, and the retarder is sodium gluconate.

[0025] Wherein, the particle size of the coal-fired slag and the blast furnace slag are both 3-10 μm; the chemical composition of the blast furnace slag includes, by mass percentage, 32.0-49.0% CaO, 32.0-41.0% SiO2, 6.0-17.0% Al2O3, 0.2-4.0% Fe2O3, 2.0-13.0% MgO, 0.1-4.0% MnO, 0.2-2.0% S, and the balance is loss on ignition; the chemical composition of the coal-fired slag includes, by mass percentage, 49.2-62.5% SiO2, 15.1-25.2% Al2O3, 5.1-16.1% Fe2O3, 0.7-4.9% CaO, 9.5-1.8% MgO, 1.3-2.8% K2O, and the balance is loss on ignition.

[0026] The preparation method comprises: taking blast furnace slag and coal-fired furnace slag according to a proportion, stirring and mixing them to obtain dry material A; adding an activator, a water reducer, a suspension stabilizer and a retarder to the dry material A in proportion, stirring them thoroughly and evenly, and grinding them to obtain a heavy oil hot mining material polymer plugging agent.

[0027] Example 2

[0028] In this embodiment, the raw materials for preparing the heavy oil thermal mining polymer plugging agent include, by weight percentage: 50 parts of blast furnace slag, 50 parts of coal-fired slag, 22 parts of activator, 3.3 parts of water reducer, 20 parts of suspension stabilizer, and 10 parts of retarder. The rest are the same as in Example 1.

[0029] Example 3

[0030] In this embodiment, the raw materials for preparing the heavy oil thermal mining polymer plugging agent include, by weight percentage: 50 parts of blast furnace slag, 50 parts of coal-fired slag, 25 parts of activator, 3.5 parts of water reducer, 30 parts of suspension stabilizer, and 20 parts of retarder. The rest are the same as in Example 1.

[0031] In an embodiment of the present invention, the raw materials for preparing the mineral polymer plugging agent include: blast furnace slag and coal-fired furnace slag, an activator, a water reducer, a suspension stabilizer (preferably 2-acrylamido-2-methylpropane sulfonic acid (AMPS)), and a retarder (preferably sodium gluconate); the activator is a mixture of sodium hydroxide and water glass, the modulus of the water glass in the activator is 1.3-1.5, and the added amount of the activator is 20% to 25% of the weight of the blast furnace slag and coal-fired furnace slag materials. The mineral aggregate adopts coal-fired furnace slag and blast furnace slag as main materials, and adopts water glass as alkaline activator. Through the interaction of the three, the early hydration reaction can be slowed down, the early setting time can be extended, and the shrinkage and cracking can be avoided, so as to form a geopolymer with low porosity and high density. The geopolymer not only has good mechanical strength and stability, but also has excellent resistance to chloride ion corrosion. The selected suspension stabilizer is 2-acrylamido-2-methylpropanesulfonic acid (AMPS), which has good temperature resistance and strong dispersing and suspending ability. The selected retarder is sodium gluconate, which can effectively delay the solidification time of the mineral aggregate and ensure the safety and stability of construction.

[0032] An indoor evaluation experiment was conducted on the polymer plugging agent for heavy oil thermal mining according to the embodiment of the present invention, as follows:

[0033] 1.1 Preparation of polymer plugging agent solution for heavy oil thermal mining

[0034] 300 g of the heavy oil thermal mining polymer plugging agent of Example 1 of the present invention was added to 1000 ml of tap water, and stirred at 11000 rpm for 20 min.

[0035] 1.2 Measurement of density of polymer plugging agent solution in heavy oil thermal mining

[0036] Density determination is carried out in accordance with the standard GB / T 16783.1-2006 "Drilling fluid field test part 1: water-based drilling fluid" "4 Drilling fluid density" or GB / T 19139-2012 "Oil well cement test method" "6.4 Another instrument and method".

[0037] Table 1 Density measurement results of polymer plugging agent solution in heavy oil thermal mining

[0038]

[0039] 1.3 Measurement of viscosity, shear force, and initial / final shear force of polymer plugging agent solution in heavy oil thermal mining

[0040] The viscosity, shear force, and initial / final shear force measurements were performed in accordance with the standard GB / T 16783.1-2006 "Drilling Fluid Field Test Part 1: Water-Based Drilling Fluid" "6 Determination of Viscosity and Shear Force Using a Direct Reading Viscometer".

[0041] Plastic viscosity, dynamic shear force, apparent viscosity and static shear force are calculated according to the following formula:

[0042]

[0043] Where: PV is plastic viscosity, mPa·s; YP is dynamic shear force, Pa; AV is apparent viscosity, mPa·s; Φ 600 , Φ 300 It is the constant reading value at 600r / min and 300r / min; G 10 or G 10min' It is the static shear force for 10s or 10min, Pa; Φ3 is the maximum reading of 3r / min after being stationary for 10s or 10min.

[0044] Table 2 Viscosity, shear force, and initial / final shear measurement results of polymer plugging agent solution in heavy oil thermal mining

[0045]

[0046]

[0047] The apparent viscosity and plastic viscosity of the solution are low, indicating that the viscosity of the flowing system is low and the pumpability is high; the large final cut indicates good stability after standing and no stratification due to the density of the added material will occur.

[0048] 1.4 Measurement of pH value of polymer plugging agent solution in heavy oil thermal mining

[0049] The pH value determination is carried out in accordance with the standard GB / T 16783.1-2006 "Drilling fluid field test part 1: water-based drilling fluid" "11 pH value".

[0050] The pH value of the system is alkaline. Construction in an alkaline environment will not corrode the pipe column and instruments and equipment, ensuring construction safety. The measured pH is 12.23.

[0051] 1.5 Measurement of initial setting / final setting time of polymer plugging agent solution in heavy oil thermal mining

[0052] The initial setting / final setting time of the heavy oil thermal mining polymer plugging agent solution was carried out by visual observation. The time when the color of the "heavy oil thermal mining polymer plugging agent solution" began to change from khaki to light green was observed was recorded as the initial setting time; the time when the color of the "heavy oil thermal mining polymer plugging agent solution" changed from khaki to light green or dark green was observed was recorded as the final setting time.

[0053] (1) Prepare the heavy oil thermal mining polymer plugging agent solution according to "1.1";

[0054] (2) injecting the heavy oil thermal mining polymer plugging agent solution in step (1) into a 200 mL transparent sealed mold, and then placing it in a constant temperature oven / constant temperature water bath, setting the temperature to 20-110° C., and recording the time when the set temperature is reached as the start time;

[0055] (3) Observe every half hour and record the initial setting / final setting time.

[0056] (4) Take the final setting sample out of the mold and place it in a constant temperature water bath (constant temperature of 70°C) for curing.

[0057] Table 3 Results of initial setting / final setting time of polymer plugging agent solution in heavy oil thermal mining

[0058]

[0059]

[0060] The initial setting time of the system at the simulated downhole temperature is the pumpable time. The longer the initial setting time, the greater the amount that can be pumped. After final setting, a dark green blocky solid with greater strength is formed.

[0061] 1.6 Measurement of volume retention rate of polymer plugging agent solution before and after solidification in heavy oil thermal mining

[0062] The volume retention rate here refers to the volume retention of the slurry after final solidification per unit volume of initial setting / final setting time.

[0063] (1) Take out the sample that has been kept at a constant temperature for 168 hours in "1.5" and place it in a measuring cup filled with a certain volume (V1) of tap water. Record the volume before and after filling (V2);

[0064] (2) Calculate the volume retention rate after 168 hours of final setting.

[0065] Table 4 Measurement results of volume retention rate of polymer plugging agent solution after solidification of heavy oil thermal mining

[0066]

[0067] After the curing module was cured at 70°C for 168 hours, the volume retention rate was above 98.5%. The greater the volume retention rate, the higher the degree of occupancy of the plugging agent in the plugging channel, and the more conducive it is to plugging the high permeability channel.

[0068] 1.7 Measurement of compressive strength of high temperature resistant long-term plugging fluid for heavy oil

[0069] The compressive strength of the heavy oil high temperature resistant long-term plugging fluid is measured using an oil and gas reservoir stress sensitivity tester. The compressive strength refers to the maximum pressure that a unit area module can withstand without side restraint.

[0070] (1) Prepare heavy oil high temperature resistant long-term plugging fluid according to "4.2.1";

[0071] (2) The heavy oil high temperature resistant long-term plugging liquid is molded and maintained at normal pressure (the curing temperature is set at 70°C, and the curing device is equipped with a stirrer) in accordance with GB / T 19139-2012 "Test Methods for Oil Well Cement" to carry out the "7 Cement Stone Compressive Strength Test";

[0072] (3) The strength test of the high temperature resistant long-term plugging fluid for heavy oil was carried out in accordance with GB / T 19139-2012 “Test Methods for Oil Well Cement” “7 Cement Stone Compressive Strength Test”.

[0073] Table 5 Compressive strength measurement results of heavy oil high temperature resistant long-term plugging fluid after solidification

[0074]

[0075]

[0076] The compressive strength of the modules after curing for 168 hr and 336 hr, the test results show that the final setting strength is large, and the compressive strength increases gradually with the longer curing time.

[0077] 1.8 Permeability measurement of polymer plugging agent solution after consolidation in heavy oil thermal mining

[0078] The permeability indicates the ability of the medium to allow fluid to pass through. According to Darcy's law, the gas permeability calculation formula is:

[0079]

[0080] Where: K-gas permeability, md; P0-atmospheric pressure, 0.1MPa; Q0-flow rate under atmospheric pressure, cm 3 / s; μ g -Gas viscosity, MPa.s; L-Rock sample length, cm; A-Rock sample cross-sectional area, cm 2 ; P1, P2-core inlet and outlet pressure, MPa.

[0081] In this experiment, the STY-Ⅱ gas permeability meter was used to measure the permeability of the polymer plugging agent solution after consolidation of heavy oil thermal mining. Experimental conditions: room temperature 20℃, nitrogen was used as the displacement medium, the nitrogen viscosity was 0.0176mpa.s, and the confining pressure system was set to 0.80MPa. The experimental steps are as follows:

[0082] (1) Take out the module that has been cured for 168 hours and cut it into standard cores (Ø25, core columns with a length of not less than 2.5 cm);

[0083] (2) Place the numbered cores into the STY-II gas permeability meter and directly test the permeability after consolidation according to the system setting steps. Replace the inlet and outlet ends of each core and test it twice to obtain the average permeability of the core.

[0084] Table 6 Core permeability measurement results after the polymer plugging agent solution of heavy oil thermal mining solidified

[0085]

[0086]

[0087] The modules were cured at 70°C (simulated downhole temperature) for 168 hours. The measured results showed that the core permeability was less than 0.1 md, indicating that there was basically no permeability after solidification.

[0088] 1.9 Experiment on the heat resistance of polymer plugging agent solution after consolidation in heavy oil thermal mining

[0089] (1) The sample cured in a 70°C constant temperature water bath for 168 hours in step 1.5 was placed in a 300°C constant temperature oil bath and cured for another 168 hours;

[0090] (2) The test volume retention rate is 98.7%;

[0091] (3) Test compressive strength: 2.53 MPa;

[0092] (4) The test core permeability is 0.03md.

[0093] The module was subjected to final setting and curing at 300°C (simulated steam temperature) for 168 hours. The measured results showed that the volume retention rate, compressive strength and permeability remained stable.

[0094] Application Examples

[0095] Example 1

[0096] Well Cheng 911-P9 in an oilfield of a certain oil production plant: Before the construction of Well Cheng 911-P9, two rounds of gas injection were carried out. Due to the top water communication and steam channeling with Well Cheng 911-P3 in the east of Cheng during the second round of gas injection, the production effect was not good, and the gas injection pressure was 15.1MPa. It was shut down in March 2020. Basic information of the oil well: effective thickness 18m; porosity 29%, high porosity and high permeability reservoir; average oil saturation is 60%; crude oil density 1.0173g / cm3; 80℃ crude oil viscosity 6252mPa.s, which is an ultra-heavy oil reservoir; the reservoir burial depth is between 1600 and 1700 meters; reservoir pressure 15.87MPa, pressure coefficient 0.917, normal pressure system; formation temperature 80℃, belonging to normal temperature system. The first round of oil production was from September to November 2019, with 2,500 tons of gas injection, 817.5 tons of cumulative oil per cycle, 1,813.3 tons of cumulative water per cycle, and 66.4% water content per cycle. The water content was 88% before entering the next round, and the cycle was switched to high water content. The second round of oil production was from December 2019 to March 2020, with 2,200 tons of gas injection, 405 tons of cumulative oil per cycle, 1,810.9 tons of cumulative water per cycle, and 81.7% water content per cycle. The water content was 95.5% before entering the next round, and the cycle was switched to high water content. Due to the high water content and steam channeling with the Cheng 911-P3 well, heavy oil thermal mining polymer plugging agents were used for water plugging and channeling after the well was shut down for one year. In April 2021, the cycle switching and water plugging construction was carried out according to the design. The gas injection was completed half a month later, and the well was started. During this period, a total of 400m of heavy oil thermal mining polymer plugging agents were injected 3 As of October 2024, the cumulative oil production has increased by more than 5,000 tons, and there has been no steam crosstalk with the Cheng 911-P3 well.

[0097] Example 2

[0098] Well CDC911-P8 of a certain oil production plant was put into production in September 2019. As of now, the cumulative oil production is 13656.9t, the cumulative water production is 33417.6t, and the current production is Ng10 layer; the cumulative produced liquid volume is 47074.5t, and the cumulative injected steam volume is 18878t. A total of 8 rounds of huff-and-puff production were carried out. The average water content of the 8th round was 89.04%, which was relatively high. It was believed that there was no formation water penetration. Construction started in July 2024, and gas injection was completed half a month later, and the well was started. During this period, a total of 400m3 of heavy oil thermal mining polymer plugging agent was injected. 3The well started production in August with a water content of 49.6%. As of October 2024, the cumulative oil production was more than 1,000 tons with an average water content of 51.6%.

[0099] The above is only a specific implementation of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application shall be based on the protection scope of the claims.

Claims

1. A polymer plugging agent for heavy oil thermal mining, characterized in that: The raw materials include: blast furnace slag, coal-fired furnace slag, activator, water reducer, suspension stabilizer, and retarder; wherein the activator is a mixture of sodium hydroxide and water glass, the modulus of the water glass in the activator is 1.3-1.5, and the added amount of the activator is 20%-25% of the total weight of the blast furnace slag and the coal-fired furnace slag.

2. The polymer plugging agent for heavy oil thermal mining according to claim 1, characterized in that: The weight ratio of the coal-fired furnace slag to the blast furnace slag is 1:

1.

3. The polymer plugging agent for heavy oil thermal mining according to claim 1, characterized in that: Measured by mass percentage, the chemical composition of the blast furnace slag includes: 32.0-49.0% CaO, 32.0-41.0% SiO2, 6.0-17.0% Al2O3, 0.2-4.0% Fe2O3, 2.0-13.0% MgO, 0.1-4.0% MnO, 0.2-2.0% S, and the remainder is loss on ignition.

4. The polymer plugging agent for heavy oil thermal mining according to claim 1, characterized in that: Calculated by mass percentage, the chemical composition of the coal-fired slag includes: 49.2-62.5% SiO2, 15.1-25.2% Al2O3, 5.1-16.1% Fe2O3, 0.7-4.9% CaO, 9.5-1.8% MgO, 1.3-2.8% K2O, and the remainder is loss on ignition.

5. The polymer plugging agent for heavy oil thermal mining according to claim 1, characterized in that: The particle sizes of the coal-fired furnace slag and the blast furnace slag are both 3-10 μm.

6. The polymer plugging agent for heavy oil thermal mining according to claim 1, characterized in that: The added amount of the water reducing agent is 3-3.5% of the total weight of the blast furnace slag and the coal-fired furnace slag; wherein the water reducing agent is a lignin sulfonate water reducing agent.

7. The polymer plugging agent for heavy oil thermal mining according to claim 1, characterized in that: The added amount of the suspension stabilizer is 20-30% of the total weight of the blast furnace slag and the coal-fired slag; wherein the suspension stabilizer is 2-acrylamide-2-methylpropane sulfonic acid.

8. The polymer plugging agent for heavy oil thermal mining according to claim 1, characterized in that: The added amount of the retarder is 5-20% of the total weight of the blast furnace slag and the coal-fired slag material; wherein the retarder is sodium gluconate.

9. The polymer plugging agent for heavy oil thermal mining according to claim 1, characterized in that: Calculated by weight percentage, the raw materials of the heavy oil thermal mining polymer plugging agent include: 50 parts of blast furnace slag, 50 parts of coal-fired furnace slag, 20 parts of activator, 3 parts of water reducer, 25 parts of suspension stabilizer, and 15 parts of retarder.

10. A method for preparing a polymer plugging agent for heavy oil thermal mining as claimed in any one of claims 1 to 9, characterized in that: The method comprises: taking blast furnace slag and coal-fired furnace slag according to a proportion, stirring and mixing them to obtain dry material A; adding an activator, a water reducer, a suspension stabilizer and a retarder to the dry material A according to a proportion, stirring them fully and evenly, and grinding them to obtain a heavy oil hot mining material polymer plugging agent.